2017
DOI: 10.1038/celldisc.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol kinase-like proteins cooperate with Pld6 in regulating sperm mitochondrial sheath formation and male fertility

Abstract: Spermatids undergo the final steps of maturation during spermiogenesis, a process that necessitates extensive rearrangement of organelles such as the mitochondria. Male infertility has been linked to mitochondrial disorder, for example, hypospermatogenesis and asthenozoospermia. However, the mechanisms that regulate mitochondrial dynamics during spermiogenesis remain largely unknown. We found the glycerol kinase (Gyk)-like proteins glycerol kinase-like 1 (Gykl1) and glycerol kinase 2 (Gk2) were specifically lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…The enzymatic function of PLD 3 , PLD 4 and PLD 5 remains unknown (the first two are ER type 2 transmembrane proteins that have two HKD motifs but lack both the PX and PH domains) (Nelson and Frohman, ). PLD 6 localizes to the outer mitochondrial membrane where it acts as a cardiolipin hydrolase to generate PA (Chen et al, ). In mammals, PLD is a key enzyme in cell signalling, the function of which is mainly attributed to its reaction product, PA, and other converted lipid mediators.…”
Section: Phospholipasesmentioning
confidence: 99%
“…The enzymatic function of PLD 3 , PLD 4 and PLD 5 remains unknown (the first two are ER type 2 transmembrane proteins that have two HKD motifs but lack both the PX and PH domains) (Nelson and Frohman, ). PLD 6 localizes to the outer mitochondrial membrane where it acts as a cardiolipin hydrolase to generate PA (Chen et al, ). In mammals, PLD is a key enzyme in cell signalling, the function of which is mainly attributed to its reaction product, PA, and other converted lipid mediators.…”
Section: Phospholipasesmentioning
confidence: 99%
“…In our opinion, an increased carbonylation of the kinases and phosphatases, PKA, PP-1γ, and GK2, observed in LQ ejaculates, may lead to abnormal phosphorylation/dephosphorylation of sperm proteins. GK2 and PP-1γ are key proteins involved in energetic metabolism and the regulation of sperm motility [ 35 , 36 ]. However, among the identified proteins, PKA is the major player responsible for the activation of sperm tyrosine kinases (with serine and threonine residues) to trigger a cascade of protein phosphorylation involved in sperm motility and capacitation.…”
Section: Discussionmentioning
confidence: 99%
“…UCRI and ATP 5B are involved in electron transfer and proton gradient formation, respectively. In turn, PKA, GK2, and PP-1γ are testis-specific isoforms of enzymes involved in sperm motility and flagella development [ 35 , 36 , 40 ]. Moreover, ODF 2 is a component of the outer dense fibres of the main cytoskeletal structure of the sperm tail, and carbonylation of this protein was also observed in our previous study in cryopreserved bull semen [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10: 200186 configurations. For instance, conventional EM demonstrated that mammalian sperm mitochondria are arranged in a tight spiral around the flagellar axoneme [39][40][41], and that the mammalian sperm axoneme is surrounded by a plethora of accessory structures that dwarf the axoneme proper [13] (figure 1b). These characteristics are general features of mammalian sperm, but details such as the number of mitochondria in the midpiece and the sizes of the accessory elements vary across species (reviewed in [12,13]).…”
Section: Conventional Em Has Contributed Greatly To Our Understandingmentioning
confidence: 99%